Effect of Three Tier Treatments on Palm Oil Fuel Ash to the Properties of Ceramic Body - Emran, Nuralya Athirah; Mohd Zaky Noh (Enhanced Knowledge in Sciences and Technology, 2024)
Palm oil fuel ash (POFA) frequently harbours an elevated concentration of silica, a pivotal constituent in the fabrication of porcelain. The aim of this study is to determine the effect of three-tier treatments of POFA on the physico-mechanical properties of porcelain. POFA underwent 3 days of grinding process using a ball mill machine at 250 rpm and was sieved with a 50 µm micro-sieve. POFA was subjected to heat treatment at 800°C for 1.3 hours. Then, it was treated with 2M hydrochloric acid (HCl) and finally was second heat treatment at same temperature and soaking time as the first. Samples are produced through mixing, pelleting, and sintering processes by varying POFA and quartz compositions (0-25 wt.%). The sintering temperature is 1150 °C with heating and cooling rate at 2 °C and 5 ° C with 1.5 hours of soaking times. The samples were measured the mass loss, volume shrinkage, porosity, bulk density, water absorption while and compressive strength. The microstructure’s study was done by employing X-Ray Diffraction (XRD) and Secondary Electron Microscopy (SEM). The three-tier treatment surpasses both the untreated and two-tier treatments, highlighting its superior outcomes. The composition of 15 wt.% of POFA showcases the utmost potential for application in porcelain. A significant mass loss of 22.18%, coupled with the most prominent volume shrinkage at 29.49 wt.% during HT2 for 15 wt.% of POFA. The minimum recorded porosity stands at 1.06%, and the pinnacle of bulk density, observed at 0.00248 g/mm³, aligns with HT2. Notably, the highest compressive strength recorded reaches 320.68 MPa. To validate these results, the research investigates the crystalline properties of POFA by analysing X-ray diffraction (XRD) patterns. And employs Scanning Electron Microscopy (SEM) for the microstructure analysis of POFA. The findings suggest that POFA holds promise as a high-strength material for porcelain tiles with diverse applications in the industry.